PENGARUH PROFITABILITAS, TINGKAT SUKU BUNGA (BI RATE), DAN HARGA EMAS DUNIA TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020. - Anesa Tania; Arifin Siagian (Jurnal Manajemen, 2022)
This study aims to determine the effect of financial performance using the Profitability ratio (ROA), then the Interest Rate (BI Rate) and the World Gold Price either simultaneously or partially on the Stock Price. This study uses Metal & Mineral Mining Subsector companies listed on the Indonesia Stock Exchange for the 2015 -2020 period. The sample in this study used purposive sampling technique. This study uses secondary data in the form of annual financial reports which are accessed through www.idx.co.id. The data analysis method used in this study used the classical assumption test, multiple linear regression, hypothesis testing, and the coefficient of determination test (R Square). The data processing in this study uses the SPSS version 24 software program. The results obtained from the F test results are Profitability, Interest Rate (BI Rate) and World Gold Prices simultaneously affect Stock Prices in Metal & Mineral Mining Subsector Companies listed on the Exchange Indonesian Securities for the 2015-2020 period. Based on the results of the t-test Profitability and Interest Rate (BI Rate) there is no effect on Share Prices in Metal & Mineral Mining Subsector Companies but World Gold Prices have an effect on Share Prices in Metal & Mineral Mining Subsector Companies listed on the Indonesia Stock Exchange for the period 2015 -2020